Development of MyCheckTime® software for perioperative safety based on Toyota's Lean Methodology. - Tafur Betancourt, Luis Alberto; Zorrilla-Vaca, Andrés; Patricia Vallejos-Medina, Lorena; Mauricio Chilatra-Fonseca, José; Carlos Angarita-Navarro, Enrique; Martínez-Gaviria, Milagros; Londoño, Alejandro; Carlos Bocanegra-Rivera, Juan; Fernando Botero-Posada, Luis; Lema-Florez, Eduardo (Colombian Journal of Anesthesiology / Revista Colombiana de Anestesiología)
Introduction: In the age of healthcare safety, compliance with checklists and time tracking in surgery continue to be a gray zone in care processes. The technology applied to approach this issue and other scenarios, may contribute to solve a problem that impacts welfare and the healthcare sector economics. Objective: To introduce the design and construction of the MyCheckTime®software that incorporates Toyota's Lean methodology under the concept of Bundles. Materials and methods: Using a conceptual map, 5 measures were incorporated into the bundle; the MyCheckTime® platform was built based on a software code developed in Java8, PHP, Javascript, HTML5, Angular4, MongoDB-MySQL databases, and Docker, Ionic, VertX, Laravel-implemented technologies. Results: A software (MyCheckTime®) was constructed based on an App available for tablets and IOS and Android system-based mobile devices; a web-based platform and a database. The software captures the patient's circuit in the surgical area in real time, and records the times in which the checklists were conducted. Conclusion: MyCheckTime® is a Lean Methodology-based software that potentially enables the surgical team to deliver more efficient, safer, and timely care, allowing real time recording of the patient's circuit in the surgery area.